Формирование одномерных обводов с закономерным изменением кривизны - Холодняк, Юлія Володимирівна; Холодняк, Юлия Владимировна; Kholodniak, Yuliia; Дмітрієв, Юрій Олексійович; Дмитриев, Юрий Алексеевич; Dmitriiev, Yurii (My University, 2014)
RU: Рассматривается способ формирования плоских дискретно представленных кривых с закономерным изменением кривизны методами вариативного дискретного геометрического моделирования. Способ предполагает формирование кривой по участкам, вдоль которых кривизна изменяется монотонно, состыкованных со вторым порядком гладкости. EN: The method of formation a planar discretely represented curves with the regular change of curvature using methods of variable discretely geometrical modeling is considered in the article. The method assumes formation a curve on sections along which the curvature changes monotonically, docked with the second order smoothness.
Formation of one-dimensional contours with regular changes of curvature
Keywords: дискретно представленная кривая; монотонное изменение кривизны; второй порядок гладкости; моделирование поверхностей; алгоритмы формирования; монотонная кривая; discretely represented curve; monotonous change of curvature; second order of smoothness